The Effect of Left Lateral Position and Squatting Position on The Progress of The Active Phase of The First Stage of Labor Among Primigravida Women at Private Practice Midwife Istikomah, Amd. Keb, Sampung Subdistrict, Ponorogo District - Diyan Wahyuningsih; Neta Ayu Andera; Nisa Aprilia Andika (STIKes Patria Husada Blitar, 2021)
Primigravida women mostly experience prolonged progress of labor due to the stiff birth canal. There are several positions of labor that may accelerate cervix dilatation process including squatting. This study aimed to determine the effect of left lateral position and squatting position on the progress of the active phase of the first stage of labor among primigravida women. This was a pre-experimental study with Pre test - post test approach. The population was all primigravida women in labor at Private Practive Midwife Istikomah, Amd.Keb., Sampung Subdistrict, Ponorogo District, takenÂ with an accidental sampling technique which obtained 9 respondents. The independent variable was labour position, while the dependent variable was duration of the active phase of the first stage of labor. The data collection instrument used here was observation sheet. The results were analyzed using Paired sample T-test (Î±=0,05). The results showed that before the application of left lateral and squatting positions in VT 1, all 9 respondents (100%) had normal labour progress and after the application of left lateral and squatting positions in VT 2, most respondents (77.8%) had labour progress in short category. The analysis obtained a p-value=0.000<Î±=0.05. Thus, there was an effect of left lateral position and squatting position on the progress of the active phase of the first stage of labor among primigravida women. The combination of squatting and left lateral positions during labour seems to accelerate the progress of the active phase of the first stage of labor with minimal side effects.